Simulation research of railway crossings with stiffness control - Jan TARGOSZ (Transport Problems, 2007)
This research presents the existing problem of railway elements and motor – vehicle road elements at their intersections. The work also concerns issues of designing and constructing railway crossings at the intersections of motor-vehicle and rail transportation. A new conception of vibroisolated railway crossing is introduced, based on the analysis of a discrete-continuous system.